2016
DOI: 10.1136/bjophthalmol-2015-307799
|View full text |Cite
|
Sign up to set email alerts
|

A novel use of reticulated hyaluronic acid (Healaflow) for hypotony eyes in patients with uveitis

Abstract: Persistent ocular hypotony is a complex and ongoing challenge faced in ophthalmology. It can result in early ocular phthisis and associated visual decline, pain and deformity. We present the first case series, in which repeated intracameral injections of highly reticulated hyaluronic acid (Healaflow) have successfully prevented the complications of ocular hypotony in the long term. We believe it is a viable management option that can bring about a significant improvement to the quality of life in this subgroup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Third, Healaflow has been used in the treatment of patients with persistent ocular hypotony and atrophy of the eyeball. 14 Our in vitro experiment also confirmed that Healaflow could continue to be attached and insoluble for at least two weeks in a 37°C water bath. Although this cannot fully simulate the changes in Healaflow in the human eye in its constant movement state, animal experiments have verified the safety and effectiveness of vitreous cavity filling in rats.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Third, Healaflow has been used in the treatment of patients with persistent ocular hypotony and atrophy of the eyeball. 14 Our in vitro experiment also confirmed that Healaflow could continue to be attached and insoluble for at least two weeks in a 37°C water bath. Although this cannot fully simulate the changes in Healaflow in the human eye in its constant movement state, animal experiments have verified the safety and effectiveness of vitreous cavity filling in rats.…”
Section: Discussionsupporting
confidence: 75%
“…It is a commercially available translucent hydrogel and has been used in glaucoma filtering surgery as a space filler and to prevent postoperative scarring. 14 Healaflow is a slow resorbable and self-degrading viscoelastic agent. The ordinary viscoelastic agent can stay for 24 hours to 48 hours, but Healaflow can stay for more than 6 months to 9 months.…”
mentioning
confidence: 99%
“…Hyaluronic acid (HA) is a linear polysaccharide composed of disaccharide units of (1,4)-βlinked glucuronic acid and (1,3)-β-linked N-acetylglucosamine [1]. Due to its unique physicochemical properties, such as high intrinsic viscosity, antioxidant properties, chain stiffness and water-holding capacity [2], HA has been used for a wide variety of medical applications, including osteoarthritis [3,4], ophthalmic surgery [5,6] and cutaneous wound healing [7,8]. In dermatology and cosmetic practices, HA has been employed to help the skin regain elasticity, turgor and moisture [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Common practice is to use intracameral injections of OVD or total ligation of the external portion of the drainage tube using non-absorbable sutures [8]. The former option may require multiple injections of OVD due to their short-lived effect, although more viscous devices such as reticulated hyaluronic acid have recently been used to prevent phthisis and maintain aesthetic appearance in pre-phthisical blind eyes with chronic hypotony [11]. One third of our cases had previous cyclo-destructive procedures, which may explain the poor resolution of hypotony in these eyes using fixed-volumes of repeated intracameral OVD injections.…”
Section: Discussionmentioning
confidence: 99%